The intent of students to vaccinate is influenced by cultural factors, peer network, and knowledge about vaccines. Issue 1 (31st December 2022) - Ilogu, Laura Chinenye; Lugovska, Olga; Vojtek, Ivo; Prugnola, Anna; Callegaro, Andrea; Mazzilli, Sara; Van Damme, Pierre
ABSTRACT: Young adults are the future vaccine decision-makers as parents or health-care professionals. To understand their attitudes and behaviors toward vaccination, we conducted a cross-sectional survey of 2079 students attending the University of Antwerp, Belgium and the University of Pisa, Italy. Principal component analysis was used to investigate associations between survey responses and the intent to vaccinate. Vaccination knowledge, attitudes, and behaviors among university students in Italy and Belgium were high. However, only one-half of respondents displayed an intent to vaccinate. High levels of knowledge, positive attitudes, and confidence in vaccines were positively associated with age, higher level of study, being a medical student, a recent vaccination experience, and not knowing trusted persons who did not believe in vaccines. Country of origin was highly correlated with the survey responses and was clustered with lifestyle, family, and data source variables, suggesting a strong modifying effect of culture and family attitudes on how vaccines are perceived in this age-group. Recent meningococcal vaccination campaigns and public discussions around mandatory vaccination in Italy may have influenced these results. We show that the intent to vaccinate was correlated with two main clusters of variables linked to culture (country, family, lifestyle), and to scholarship (knowledge, attitudes, data source) that together influence the behavior of students with respect to vaccination. Our study reinforces previous findings that knowledge about vaccines is key to shaping attitudes and behaviors, but also shows that cultural and lifestyle factors are another platform that could be leveraged in promoting vaccination among young people.